Development and Evaluation of Advanced Morphological Algorithms for Automated Fish Measurement in Sustainable Fisheries - Gonçalves, Jáder Louis de Souza; Dória, Carolina Rodrigues da Costa; Watanabe, Carolina Yukari Veludo (Anais Estendidos da Conference on Graphics, Patterns and Images (SIBGRAPI), 2025)
Accurate identification and measurement of fish populations present critical challenges in ecosystems characterized by significant morphological variability. This work presents morphological algorithms developed to enhance automated fish measurement processes in freshwater fisheries, with potential applications in coastal and marine ecosystems. Key contributions include developing algorithms tailored for non-linear morphologies and integrating these advancements into the ”ICTIOBIOMETRIA” application, which systematically records fish biometric data such as weight, dimensions, and capture locations. The dataset used originated from three primary sources: images inherited from prior collaborators, samples collected in partnership with the Ichthyology and Fisheries Laboratory at the Federal University of Rondônia, and acquisitions from fish markets. These sources provided 588 images representing diverse fish species from the Madeira River basin in Porto Velho, Rondônia, located in the Western Amazon. A dataset from established authors was also used as a reference to validate the proposed measurement models, ensuring a comprehensive comparative analysis that reinforced the robustness of the developed methods. To address challenges posed by larger fish and those exhibiting non-linear shapes, algorithms were developed and implemented to manage these characteristics effectively. Among the three measurement methods evaluated, the skeletonization method demonstrated superior performance, reducing the relative total error by 1.56%, and demonstrating robustness across diverse morphologies.